A Depiction of Gender Role in the Movie of Incredibles 2 (2018) - Raihan Nurul Fahira; Ririn Kurnia Trisnawati; Muhammad Taufiqurrohman (CALL, 2020)
The research aims to figure out the gender roles which are used to look at how the film constructs and upholds gender roles. The qualitative method is used to analyze the data in which the primary data are taken from Brad Bird’s Incredibles 2 (2018). Additionally, the researcher used gender roles and cinematography theory to look at how gender is a performance and also to gain a result that gender roles are changing overtimes. The use of Judith Butler’s theory of performativity is to show that the portrayal of gender roles in the movie is slightly different from social construction. Butler’s notion of performativity refers to an act of performance that an individual is doing repeatedly as described in Incredibles 2 (2018) where Bob and Helen do the gender role reversal and share the same responsibilities in the family. Bob is previously shown as the breadwinner of the family and the main earner while Helen is a full-time stay-at-home mother who takes care of the children and the house. Since they no longer hold the traditional gender role; therefore, the movie demonstrates how they start to swap gender assigned tasks. Accordingly, the gender roles are showcased as Bob is being the househusband and the caretaker of the family while Helen is a working woman.